HIV/AIDS workplace policy development and implementation in a selected sample of South African organisations - Laas, Anja (Stellenbosch : Stellenbosch University, 2009)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--Stellenbosch University, 2009.